Important mathematical competences for students in the age of generative artificial intelligence: proof comprehension and evaluation, and ChatGPT - Stylianides, AJ; Stylianides, GJ (Ελληνική Μαθηματική Εταιρεία [Hellenic Mathematical Society], 2025)
The rapid growth and popularity of generative artificial intelligence has influenced all aspects of life and education, including mathematics education. Specifically, generative Large Language Models (LLMs), notably ChatGPT, are becoming increasingly popular among students and are changing the landscape of what mathematical competences students need in order to function effectively in the age of generative artificial intelligence and interact productively with the new technologies. We contend that educational systems must adapt to the new realities by resetting priorities, reorganizing curricula, and retraining teachers. In this paper, we call attention to the increased importance gained by two competences in the area of proof, proof comprehension and proof evaluation, as students interact with ChatGPT. We view our discussion of these proof competences as a case in point of the pressing need for mathematics education researchers and practitioners to reflect on what constitute important mathematical competences for students in the age of generative artificial intelligence. This is a foundational step that can serve as the basis for discussions about reimagining the future shape and role of mathematics education in society, including the training of teachers. Η ταχεία ανάπτυξη και η δημοτικότητα της παραγωγικής τεχνητής νοημοσύνης έχουν επηρεάσει όλες τις πτυχές της ζωής και της εκπαίδευσης, συμπεριλαμβανομένης της μαθηματικής εκπαίδευσης. Συγκεκριμένα, τα παραγωγικά Μεγάλα Γλωσσικά Μοντέλα (Large Language Models∙ LLMs), ιδιαίτερα το ChatGPT, γίνονται όλο και πιο δημοφιλή μεταξύ των μαθητών και μαθητριών, αλλάζοντας το τοπίο ως προς τις μαθηματικές δεξιότητες που χρειάζονται ώστε να λειτουργούν αποτελεσματικά στην εποχή της παραγωγικής τεχνητής νοημοσύνης και να αλληλεπιδρούν παραγωγικά με τις νέες τεχνολογίες. Πιστεύουμε ότι τα εκπαιδευτικά συστήματα δεν έχουν άλλη επιλογή από το να αναθεωρήσουν τις προτεραιότητές τους και να αναδιοργανώσουν τόσο τα αναλυτικά προγράμματα όσο και την εκπαίδευση των εκπαιδευτικών. Σε αυτή την εργασία, εστιάζουμε στη διαρκώς αυξανόμενη σημασία δύο δεξιοτήτων στον τομέα της απόδειξης, την κατανόηση της απόδειξης και την αξιολόγηση της απόδειξης, καθώς οι μαθητές και μαθήτριες αλληλεπιδρούν με το ChatGPT. Η συζήτησή μας για αυτές τις δεξιότητες απόδειξης αποτελεί χαρακτηριστικό παράδειγμα που